Surviving a Cyberattack : Securing Social Media and Protecting Your Home - Todd, Shipley; Art, Bowker (Mercury Learning and Information, 2024)
Surviving a Cyberattack: Securing Social Media and Protecting Your Home is a roadmap to navigating the internet with confidence. This comprehensive guide addresses the ever-growing challenges users face in the online world. It explores various online risks, from social media scams and data breaches to online fraud. Recognizing these threats is crucial for protecting yourself, your loved ones, and even your small business. This hands-on reference equips you with the knowledge and tools needed to navigate the online landscape safely. It covers essential topics like securing your router and social media accounts, protecting personal information, and mitigating risks for children and vulnerable adults. Additionally, it offers valuable insights on online shopping safety, responsible technology disposal, and surviving a cyberattack. You'll learn about Safeguarding devices and how to master router configuration, identifying IoT risks, and creating impenetrable defenses. Navigating social media and securing accounts, understanding privacy settings, and banishing social media scams. Protecting your children and how to foster responsible online habits, managing their digital access, and keeping them safe from harm. Securing a small business and shielding data from cyberattacks, avoiding business scams, and ensuring responsible social media use. Caring for vulnerable family members and protecting them from online predators, managing their digital accounts, and handling sensitive topics like digital estate planning. Bouncing back from attacks and learning how to properly use data backup practices, understand reporting procedures, and emerge stronger from any digital mishap.